Assessment of retinal and choroidal structural and microvascular changes in early diabetic retinopathy using swept-source optical coherence tomography angiography - Jin Jiang; Xiaole Wang; Hongjun Bian (PLoS ONE, 2025)
Objective It was to assess changes in structural parameters in early diabetic retinopathy (DR). Materials and methodologies This study is a retrospective analysis that included patients with early DR admitted to the Affiliated Third Hospital of Nantong University from January 2024 to December 2024. The participants were divided into the non-DR group (NDR group) and the non-proliferative DR group (NPDR group, which included mild, moderate, and severe subgroups) using swept-source optical coherence tomography angiography (SS-OCTA) technology. One-way analysis of variance (ANOVA) and the Kruskal-Wallis test were used to compare parameter differences among the groups. Results A total of 208 diabetic patients were included (55 in the NDR group, 153 in the NPDR group) and 51 healthy controls. The results showed that the FAZ area in the NPDR group was significantly larger than that in the control group (CG) (mean difference: +0.38 ± 0.10 mm2, 95% CI [0.25-0.51], P < 0.001), and it was positively correlated with disease severity (trend test P < 0.001). Relative to the CG, NDR group and various stages of NPDR group exhibited greatly lower values in choroidal vascular index (CVI), peripapillary vascular density (ppVD), peripapillary retinal nerve fiber layer thickness (pRNFL), vascular density (VD) in both the superficial and deep retinal vascular complexes, total perfusion area (PA), small vessel density (SVD), disc area, vascular density (FD300) within a 300 µm radius of the foveal center, and capillary plexus blood flow density (P<0.05). NPDR group showed progressively lower values than NDR group, with severity increasing as the condition worsened (P<0.05). Conclusion SS-OCTA can effectively monitor changes in structural parameters and serves as a valuable tool for evaluating the progression of early DR.